The Responsibility to Protect in Rakhine State - Bartošová, Petra (2019)
The main aim of this thesis is to examine the Rohingya crisis in Myanmar’s Rakhine State through the Responsibility to Protect principle. The Responsibility to Protect emerged in 2001 as a response to mass atrocity crimes in 1990s. In 2005, the international community endorsed the Responsibility to Protect at the 2005 World Summit. Since then, various authors have tried to develop guidelines on how the Responsibility to Protect might be implemented in practice. Most significantly, the former Secretary-General Ban Ki-moon defined three pillars to the Responsibility to Protect. Therefore, the thesis explores these three pillars and applies them to the Rohingya. The first chapter primarily explores the background of the Responsibility to Protect and its pillars. The second chapter applies the three pillars to the Rohingya, a Muslim group of Rakhine State, who have long suffered from discrimination and persecution. The first two pillars analyse the situation in Rakhine State before August 25, 2017 when the current crisis started resulting in massive exodus to neighbouring Bangladesh. The third pillar further analyses the international community’s response to the crisis during which the crimes covered by the Responsibility to Protect may have been committed.